Modified Slenderness Ratio for Built-up Members - Sato, Atsushi; Uang, Chia-Ming (Engineering Journal, 2007)
Based on a review of theory, background for the historical development of the AISC specifications, and an updated experimental database, a simple model which maintains the accuracy for the calculation of the modified slenderness ratio of built-up members with closely spaced individual components (for example, double angles and double channels) that are connected by welded or pretensioned bolted connectors is proposed.